2003
DOI: 10.1002/jcb.10436
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory T cells rapidly induce differentiation of human bone marrow stromal cells into mature osteoblasts

Abstract: Activated T cells secrete multiple osteoclastogenic cytokines which play a major role in the bone destruction associated with rheumatoid arthritis. While the role of T cells in osteoclastogenesis has received much attention recently, the effect of T cells on osteoblast formation and activity is poorly defined. In this study, we investigated the hypothesis that in chronic inflammation activated T cells contribute to enhanced bone turnover by promoting osteoblastic differentiation. We show that T cells produce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 43 publications
2
70
0
1
Order By: Relevance
“…It has been suggested that inflammation promotes osteoblast differentiation directly or indirectly (Rifas et al, 2003;Gortz et al, 2004;Shen et al, 2005). Inflammation caused by the surgical procedure may have initiated differentiation of osteoblasts and enhanced their production and degradation of ECM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that inflammation promotes osteoblast differentiation directly or indirectly (Rifas et al, 2003;Gortz et al, 2004;Shen et al, 2005). Inflammation caused by the surgical procedure may have initiated differentiation of osteoblasts and enhanced their production and degradation of ECM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…RANK expression has been described in osteosarcoma-derived cell lines (20) together with bone marrow stromal cells and osteoblasts (21). Cathepsin K, a cysteine protease expressed by osteoclasts, appears to be essential for osteoclast-mediated collagen type-I degradation (22).…”
Section: Discussionmentioning
confidence: 99%
“…In the present POS-1 osteosarcoma model, POS-1 cells express RANK, not RANKL. RANK is known to be predominantly present at the surface of osteoclasts and some immune cells (28), but its expression has also been revealed in marrow stromal cells and osteoblasts and was strongly up-regulated when activated by T-cell conditioned medium (21). Another publication from Miyamoto et al reported that human osteosarcoma-derived cell lines expressed both RANK and RANKL mRNAs but the functionality of the receptor, RANK, was not investigated (20).…”
Section: Discussionmentioning
confidence: 99%
“…CCR6 is expressed on several cell types commonly found in the bone marrow environment, including macrophages and T cells. Given the reported ability of BMM and T cells to facilitate osteoblast differentiation and survival, (25)(26)(27)(28)(29)(30)(31) we examined the ability of CCL20 to promote the recruitment of these cells. BMM or T cells isolated from Ccr6 -/-and WT mice were plated in the top chamber of transwell filter units, whereas CCL20, osteoblasts, or osteoblast-conditioned media were placed in the lower chamber.…”
Section: Ccl20/ccr6 Signaling Promotes Osteoblast Survivalmentioning
confidence: 99%